Electrical conductivity behavior of epoxy matrix nanocomposites with simultaneous dispersion of carbon nanotubes and clays - Sene T.S.* (2016)
© 2014 Society of Plastics Engineers.In this work, nanocomposites with simultaneous dispersion of multiwalled carbon nanotubes (MWCNT) and montmorillonite clays in an epoxy matrix were prepared by in situ polymerization. A high energy sonication was employed as the dispersion method, without the aid of solvents in the process. The simultaneous dispersion of clays with carbon nanotubes (CNT) in different polymeric matrices has shown a synergic potential of increasing mechanical properties and electrical conductivity. Two different montmorillonite clays were used: a natural (MMT-Na+) and an organoclay (MMT-30B). The nanocomposites had their electrical conductivity (σ) and dielectric constant (ϵr) measured by impedance spectroscopy. The sharp increase in electrical conductivity was found between 0.10 and 0.25 wt% of the MWCNTs. Transmission electron microscopy (TEM) of the samples showed a lower tendency of MWCNT segregation on the MMT-30B clay surface, which is connected to intercalation/exfoliation in the matrix, that generates less free volume available for MWCNTs in the epoxy matrix. Data from electrical measurement showed that simultaneously adding organoclay reduces the electrical conduction in the nanocomposite. Moreover, conductivity and permittivity dispersion in low frequency suggest agglomeration of nanotubes surrounding the natural clay (MMT-Na+) particles, which is confirmed by TEM.